Led Therapy In Complex Treatment of Acute Paraproctitis - Sherkulov K.U.; Usmonkulov M.K.; Babakulova F.U. (Journal of Medical Genetics and Clinical Biology, 2024)
One of the most common diseases in emergency proctology is acute paraproctitis, the incidence of which, according to our data, occupies a leading position in the structure of proctological diseases. The number of these patients and the increasing resistance of microbes require the development of more effective treatments. A fundamentally new direction here is phototherapy. As part of studying the effect of phototherapy on the course of an acute purulent-inflammatory process and the dynamics of wound healing, a study was performed on 75 laboratory rats. It has been proven that photodynamic therapy has an antibacterial effect and accelerates reparative processes. The data obtained formed the basis for the clinical part of the study.